2010
DOI: 10.1590/s1676-06032010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Potential seed dispersal by Didelphis albiventris (Marsupialia, Didelphidae) in highly disturbed environment

Abstract: Potential seed dispersal by Didelphis albiventris (Marsupialia, Didelphidae) in highly disturbed environment. Biota Neotrop. 10(2): http://www.biotaneotropica. org.br/v10n2/en/abstract?article+bn00610022010.Abstract: Urban forests are usually isolated and highly disturbed, however they are important shelters for tolerant animal species. Their food habits expose the different ecological roles these animals perform in the habitat. We analyzed the contribution of Didelphis albiventris Lund (1840), as a seed dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 41 publications
1
42
0
12
Order By: Relevance
“…However, despite the fact that changes in the probabilities of seed germination after gut passage comprise an important component of seed dispersal and effectiveness (Traveset & Verdu 2002;Silveira et al 2012b), increased germination is not a general rule for seeds consumed by didelphid dispersers (Cáceres & Lessa 2012, present study). Recent studies indicate that the passage of seeds through the digestive tract of D. albiventris and G. agilis does not always improve seed germinability (see Cantor et al 2010;Camargo et al 2011, respectively). Our germination experiments revealed that, although the CG -control group.…”
Section: Germinabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…However, despite the fact that changes in the probabilities of seed germination after gut passage comprise an important component of seed dispersal and effectiveness (Traveset & Verdu 2002;Silveira et al 2012b), increased germination is not a general rule for seeds consumed by didelphid dispersers (Cáceres & Lessa 2012, present study). Recent studies indicate that the passage of seeds through the digestive tract of D. albiventris and G. agilis does not always improve seed germinability (see Cantor et al 2010;Camargo et al 2011, respectively). Our germination experiments revealed that, although the CG -control group.…”
Section: Germinabilitymentioning
confidence: 99%
“…When didelphids accelerate seed germination (as in the case of C. urceolata), ingested seeds germinate in higher proportions than do non-ingested seeds, probably as a result of seed coat scarification (Robertson et al 2006;Lessa & Cáceres 2012). Many factors related both to the intrinsic plant and disperser traits may influence the outcomes of seed passage through the digestive tract of potential vertebrate dispersers (Traveset & Verdú 2002;Rodrigues-Peréz et al 2005), such as seed size, fruit color, experimental conditions, disperser taxon, habitat structure and vegetation composition, or a combination of such factors (Traveset & Verdu 2002;Cantor et al 2010;Cáceres & Lessa 2012). All these factors, together or alone, can explain the differences observed between the germination of seeds found in the samples and the control group.…”
Section: Germinabilitymentioning
confidence: 99%
See 3 more Smart Citations